If 5+√3 /5-√3 =a+b, find rational number,a and b.
Answers
Answered by
5
By Rationalization,
On comparing values,
I hope this will help you
(-:
Answered by
4
Hello friends!!
Here is your answer :
![\frac{5 + \sqrt{3} }{5 - \sqrt{3} } = a + b \frac{5 + \sqrt{3} }{5 - \sqrt{3} } = a + b](https://tex.z-dn.net/?f=+%5Cfrac%7B5+%2B+%5Csqrt%7B3%7D+%7D%7B5+-+%5Csqrt%7B3%7D+%7D+%3D+a+%2B+b+)
First we have to rationalise the denominator..
![\frac{5 + \sqrt{3} }{5 - \sqrt{3} } \: \times \frac{5 + \sqrt{3} }{5 + \sqrt{3} } \frac{5 + \sqrt{3} }{5 - \sqrt{3} } \: \times \frac{5 + \sqrt{3} }{5 + \sqrt{3} }](https://tex.z-dn.net/?f=%5Cfrac%7B5+%2B+%5Csqrt%7B3%7D+%7D%7B5+-+%5Csqrt%7B3%7D+%7D+%5C%3A+%5Ctimes+%5Cfrac%7B5+%2B+%5Csqrt%7B3%7D+%7D%7B5+%2B+%5Csqrt%7B3%7D+%7D+)
![\frac{(5 + \sqrt{3} )(5 + \sqrt{3}) }{(5 - \sqrt{3} )(5 + \sqrt{3} )} \frac{(5 + \sqrt{3} )(5 + \sqrt{3}) }{(5 - \sqrt{3} )(5 + \sqrt{3} )}](https://tex.z-dn.net/?f=%5Cfrac%7B%285+%2B+%5Csqrt%7B3%7D+%29%285+%2B+%5Csqrt%7B3%7D%29+%7D%7B%285+-+%5Csqrt%7B3%7D+%29%285+%2B+%5Csqrt%7B3%7D+%29%7D+)
![\frac{{(5 + \sqrt{3})}^{2} }{(5 - \sqrt{3})(5 + \sqrt{3}) } \frac{{(5 + \sqrt{3})}^{2} }{(5 - \sqrt{3})(5 + \sqrt{3}) }](https://tex.z-dn.net/?f=%5Cfrac%7B%7B%285+%2B+%5Csqrt%7B3%7D%29%7D%5E%7B2%7D+%7D%7B%285+-+%5Csqrt%7B3%7D%29%285+%2B+%5Csqrt%7B3%7D%29+%7D)
Using identity
( x + y )² = x² + y² + 2xy
( x + y ) ( x - y ) = x² - y²
![\frac{ {(5)}^{2} + {( \sqrt{3}) }^{2} + 2(5)( \sqrt{3} )}{ {(5)}^{2} - {( \sqrt{3} )}^{2} } \frac{ {(5)}^{2} + {( \sqrt{3}) }^{2} + 2(5)( \sqrt{3} )}{ {(5)}^{2} - {( \sqrt{3} )}^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7B%285%29%7D%5E%7B2%7D+%2B+%7B%28+%5Csqrt%7B3%7D%29+%7D%5E%7B2%7D+%2B+2%285%29%28+%5Csqrt%7B3%7D+%29%7D%7B+%7B%285%29%7D%5E%7B2%7D+-+%7B%28+%5Csqrt%7B3%7D+%29%7D%5E%7B2%7D+%7D+)
![\frac{25 + 3 + 10 \sqrt{3} }{25 - 3} \frac{25 + 3 + 10 \sqrt{3} }{25 - 3}](https://tex.z-dn.net/?f=+%5Cfrac%7B25+%2B+3+%2B+10+%5Csqrt%7B3%7D+%7D%7B25+-+3%7D+)
![\frac{28 + 10 \sqrt{3} }{22} \frac{28 + 10 \sqrt{3} }{22}](https://tex.z-dn.net/?f=+%5Cfrac%7B28+%2B+10+%5Csqrt%7B3%7D+%7D%7B22%7D+)
![\frac{28}{22} + \frac{10 \sqrt{3} }{22} \frac{28}{22} + \frac{10 \sqrt{3} }{22}](https://tex.z-dn.net/?f=+%5Cfrac%7B28%7D%7B22%7D+%2B+%5Cfrac%7B10+%5Csqrt%7B3%7D+%7D%7B22%7D+)
![\frac{14}{11} + \frac{5 \sqrt{3} }{11} \frac{14}{11} + \frac{5 \sqrt{3} }{11}](https://tex.z-dn.net/?f=+%5Cfrac%7B14%7D%7B11%7D+%2B+%5Cfrac%7B5+%5Csqrt%7B3%7D+%7D%7B11%7D+)
On comparing these values,
![a = \frac{14}{11} a = \frac{14}{11}](https://tex.z-dn.net/?f=a+%3D+%5Cfrac%7B14%7D%7B11%7D+)
![b = \frac{5 \sqrt{3} }{11} b = \frac{5 \sqrt{3} }{11}](https://tex.z-dn.net/?f=b+%3D+%5Cfrac%7B5+%5Csqrt%7B3%7D+%7D%7B11%7D+)
Hope it helps you.. ☺️☺️☺️☺️
# Be Brainly
Here is your answer :
First we have to rationalise the denominator..
Using identity
( x + y )² = x² + y² + 2xy
( x + y ) ( x - y ) = x² - y²
On comparing these values,
Hope it helps you.. ☺️☺️☺️☺️
# Be Brainly
Similar questions